Astronomy - Green, Dan. (New York : Kingfisher, 2009)
Contains individual profiles of major celestial bodies and concepts in the universe, each with scientific facts and an anime-style portrait.
Cover title.
Includes index.
Includes Solar System poster.
Library Media Connection, November 2009.
School Library Journal, August 2009.
Voice of Youth Advocates (V.O.Y.A.), December 2009.
Keywords: Astronomy -- Juvenile literature; Astronomy; Astronomy